The impact of polyhedron learning assisted by Edpuzzle in improving students' mathematical representation - Nenden Suciyati Sartika; Yaya S. Kusumah; Bambang Avip Priatna Martadiputra; Sutihat Sutihat; Eka Rosdianwinata (Universitas Hamzanwadi, 2023)
The ability that students must have is the ability of mathematical representation. This research aims to determine if eighth-grade students at Al-Qona'ah Islamic Junior High School improve their mathematical representation skills after using the Edpuzzle application to learn how to construct polyhedrons. It was a quantitative research design using the Quasi Experiment research method with control and experimental classes. This research's population comprised 60 students (23 males and 37 females). After conducting research, it was determined that students' mathematical representation abilities did not improve with the aid of the Edpuzzle application on the polyhedron due to the need for more learning support facilities when utilizing the Edpuzzle application. This research is supported by the t-test, which yielded t-count < t-table or -29.2936 < -1.67155 so that H0 is accepted. The results of the n-gain calculation yielded a total n-gain score of 0.03, or the n-gain was low, indicating was no progress in learning using the Edpuzzle application on the polyhedron. This study did not have an impact on increasing students' mathematical representation.